1987
DOI: 10.1111/j.1528-1157.1987.tb05769.x
|View full text |Cite
|
Sign up to set email alerts
|

Monotherapy with Valproate in Primary Generalized Epilepsies

Abstract: Sodium valproate enteric-coated tablets were administered as monotherapy to 118 patients (median age, 19 years) with primary generalized epilepsies. More than half (56%) of these patients were transferred from prior drug therapy, most of them because of inadequate seizure control, and some because of adverse effects. Seventy-one percent of the patients experienced tonic-clonic seizures, either alone or in combination with other types of seizures, principally absences. Mean duration of follow-up was 18 months (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(50 citation statements)
references
References 11 publications
0
49
0
1
Order By: Relevance
“…Like VPA, ESM suppresses absence seizures in >80% of patients [11,Class II]. ESM may be a useful adjunct in the treatment of myoclonic seizures in PGE [12,Class III].…”
Section: Drugs With Proven Efficacy In Pge Treatment Ethosuximidementioning
confidence: 99%
“…Like VPA, ESM suppresses absence seizures in >80% of patients [11,Class II]. ESM may be a useful adjunct in the treatment of myoclonic seizures in PGE [12,Class III].…”
Section: Drugs With Proven Efficacy In Pge Treatment Ethosuximidementioning
confidence: 99%
“…AED monitoring could thus confirm the presence of "false" intractable epilepsies. Many studies showed that, in about 80% of cases, it was possible to achieve good control of seizures in patients after a first seizure by prescribing only one AED (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Such monotherapy permitted comparison of the efficacy and toxicity of drugs used for initial treatment: VPA, CBZ, PHT, PB, and primidone…”
Section: Dogmatic Monotherapymentioning
confidence: 99%
“…However, there is little general consensus on the qualitative and quantitative characteristics of these effects. Clinical data suggest that VPA has both immediate and longer-lasting effects: although it effectively treats status epilepticus (Sirven and Waterhouse, 2003), there is poor correlation between plasma levels and clinical efficacy (Burr et al, 1984;Chadwick, 1985;Sundqvist et al, 1998), effective seizure control may only be achieved after days or weeks of treatment (Henriksen and Johannessen, 1982;Bourgeois et al, 1987), and effects may persist after cessation of treatment (Rowan et al, 1979).…”
Section: Introductionmentioning
confidence: 99%